2012
DOI: 10.1016/j.neuroimage.2011.08.019
|View full text |Cite
|
Sign up to set email alerts
|

High field magnetic resonance microscopy of the human hippocampus in Alzheimer's disease: Quantitative imaging and correlation with iron

Abstract: We report R2 and R2* in human hippocampus from five unfixed post-mortem Alzheimer’s disease (AD) and three age-matched control cases. Formalin-fixed tissues from opposing hemispheres in a matched AD and control were included for comparison. Imaging was performed in a 600 MHz (14T) vertical bore magnet at MR microscopy resolution to obtain R2 and R2* (62 μm × 62 μm in-plane, 80 μm slice thickness), and R1 at 250 μm isotropic resolution. R1, R2 and R2* maps were computed for individual slices in each case, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 62 publications
(98 reference statements)
3
67
1
Order By: Relevance
“…MRI scans of post-mortem human brains and a mouse model of Alzheimer’s disease show decreases in hippocampal T 2 * MRI, which is sensitive to the magnetic properties of iron 86,87 or its spatial variance, attributed in part to iron in Aβ plaques. 8890 Although MRI resolution is not sufficient to detect individual plaques, T 2 * abnormalities that result from plaque aggregates might be detected with MRI. When clearly distinguished from potential confounders originating from haem iron, changes in hippocampal T 2 *-weighted MRI might be a valuable accompaniment to morphological changes in the development of a biomarker for the early stages of Alzheimer’s disease.…”
Section: Iron In Neurodegenerative Disordersmentioning
confidence: 99%
“…MRI scans of post-mortem human brains and a mouse model of Alzheimer’s disease show decreases in hippocampal T 2 * MRI, which is sensitive to the magnetic properties of iron 86,87 or its spatial variance, attributed in part to iron in Aβ plaques. 8890 Although MRI resolution is not sufficient to detect individual plaques, T 2 * abnormalities that result from plaque aggregates might be detected with MRI. When clearly distinguished from potential confounders originating from haem iron, changes in hippocampal T 2 *-weighted MRI might be a valuable accompaniment to morphological changes in the development of a biomarker for the early stages of Alzheimer’s disease.…”
Section: Iron In Neurodegenerative Disordersmentioning
confidence: 99%
“…74 Alzheimer disease (AD) has also been associated with disrupted iron metabolism in the brain, and iron accumulates in the rims of amyloid-β (Aβ) plaques 75 and in neurofibrillary tangles. 76 Despite some suggestion of citation bias with respect to iron accumulation in AD, 77 several studies [78][79][80][81] have confirmed that iron levels are elevated in various brain regions in this disease. Cortical accumulation of iron has also been identified in acute relapses of multiple scler osis; paradoxically, however, iron levels decrease in chronic cases.…”
Section: Iron In the Ageing Brainmentioning
confidence: 99%
“…Dysfunctional brain iron homeostasis is believed to play an important role in Alzheimer's disease (AD) [3]. Iron accumulation is seen in the AD postmortem brain [4] and iron content correlates with disease duration and Mini-Mental State Examination (MMSE) score [5,6]. Individuals with mild cognitive impairment (MCI) with high risk of AD, showed higher cortical iron in vivo using MRI (measured using quantitative susceptibility mapping techniques), which spatially co-localized with A␤ plaques and correlated with higher plaque load [7].…”
Section: Introductionmentioning
confidence: 99%